Antibacterial Effect of Virgin and Refined Coconut Oils on Pathogenic Bacteria: A Review - Manar Saad Hussain1 , Farah Tareq Al-Alaq2 , Noor Salman Al-Khafaji2 , Hussein O. M. Al-Dahmoshi2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Virgin coconut oil (VCO) is the most oldest edible oil, extracted from fresh and mature kernel using wetor dry methods, therefor the resulting oil is a pure, clear, and colorless with a scent of fresh coconut, thesecharacteristics make VCO has the preferableness in medical and health applications, over refining coconutoil (RCO) that is extract from kernel of coconut after drying by methods makes the oil refining, bleaching anddeodorizing. In spite of that, the chemical compositions particularly the fatty acids in both VCO and RCOare the same with no significant difference. MCFAs which are classified as MCTs, are the basic componentsin both VCO and RCO, these MCFAs particularly lauric acid (LA) following by capric and caprylic acidsplaying a great role in antimicrobial activity of coconut oil, therefor the extraction of these fatty acids areshow more antibacterial activity on pathogenic bacteria more than lipolyzed VCO or VCO itself that maynot show inhibition effect. Gram positive bacteria is more sensitive than gram negative one towards LAand other fatty acids, therefor these fatty acids at high concentrations showed inhibition effect on gramnegative bacteria, while at low concentration showed resistance. This study attempts to review the chemicalcomponents in both VCO and RCO based on their extraction methods, also the antibacterial activity andthe mechanism of action, also suggests that RCO has the same effect as antibacterial as VCO based on theirchemical compositions.